Isolation, characterization and application of micro-satellite markers in Persian Sturgeon, acipenser persicus borodine - Moghim, Mehdi (2013)
The Persian sturgeon (Acipenser persicus) is one of the most valuable genetic resources, which is an endangered species. The development of a conservation program for this species requires knowledge of its genetic diversity obtained by using a reliable molecular marker system to ascertain its population genetic structure. Developing such markers in sturgeons that have polyploid ancestry is particularly challenging because many markers exhibit polysomic inheritance. For this purpose, several experiments were conducted to develop single locus deoxyribonucleic acid (DNA) microsatellite markers for the Persian sturgeon. An enriched library was prepared based on a modified biotin-capture method. Approximately, 1800 positive clones were screened. Out of these, 68 microsatellites primer pairs were designed and tested for use in the Persian sturgeon. While none of the loci amplified showed disomic inheritance in the Persian sturgeon, several of them appeared useful for studies of stellate sturgeon (Acipenser stellatus), ship sturgeon (Acipenser nudiventris), beluga (Huso huso) and Russian sturgeon (Acipenser gueldenstaedtii). Another approach namely cross species amplification was then used in the quest for disomically inherited microsatellite loci in the Persian sturgeon. For this purpose, 56 and 38 sets of microsatellite primer pairs developed in shovelnose (Scaphirhynchus platorynchus) and lake (Acipenser fulvescens) surgeons respectively were used in this study. Ninety four loci were successfully amplified and thirteen microsatellite loci that were polymorphic disomic loci were identified. This is the first report of disomic loci in the Persian sturgeon. For inheritance studies of these disomic loci, two F1 families of 23 and 28 larvae were produced in 1x1 crosses of the Persian sturgeons. Eleven microsatellite loci were used for genotyping parents and their offspring. This study verified the Mendelian inheritance and disomic segregation of all the investigated loci. The microsatellite markers developed and characterized here open a new perspective for generating fundamental data to devise sound conservation strategies for the polyploid Persian sturgeon and to provide assistance to wild stock enhancement programs for the species in the Caspian Sea. The findings obtained in the present study attest to the usefulness of the investigated microsatellites for parentage control in the Persian sturgeon. To evaluate the genetic diversity of the Persian sturgeons using 11 single locus DNA microsatellite markers, 167 sturgeon fish were randomly collected from Turkmenistan, Russia, Iran and the Sefid-Rud River region. The size number of the population of specific alleles ranged from 3 to 21 alleles. The mean values of observed heterozygosity were 0.56±0.20, 0.64±0.14, 0.67±0.16, and 0.64±0.11 in Turkmenistan, Russia, Sefid-Rud and Iran populations, respectively. It was also found that the observed heterozygosity is lower than the expected heterozygosity. This means that there is still inbreeding in the Persian sturgeon and a proper breeding program is essential to avoid increasing inbreeding in natural stocks. The Analysis of Molecular Variance (AMOVA) of microsatellites revealed that there are variations among populations and among individuals within populations Cluster analysis using admixture model showed evidence of similarity among all the investigated populations. The present analysis of investigated loci showed low or no genetic differentiation or low structuring across populations at all loci between populations.